KAJIAN DEKORATIF INTERIOR PEMBATAS RUANG DENGAN MEDIA TANAMAN HIAS PADA RUMAH TINGGAL DENGAN PENDEKATAN SUSTAINABELE DESAIN - Anggi Dwi Astuti (Narada : Jurnal Desain dan Seni, 2021)
The development of interior design and decoration is growing rapidly, and all interior spaces need interior decoration. Room decoration is an important element in beautifying the room. This research discusses the study of interior decorative room dividers with ornamental plant media in residential homes with a sustainable design approach. The method used is environmentally friendly space decorative elements with a design trend in 2020, namely Tropical Vibe, which can be interpreted as decorating a house with plants. The plants selected are indoor plants that do not require direct sunlight, with varying plant sizes. The space elements that are applied make the psychology of space more lively and colorful. This study seeks to discuss how (1) Expression of design by combining interior decoration with ornamental plants (2) Providing an alternative space divider with plant media (3) Linking decorative design with the concept of sustainable design. The results of this study indicate that the design with the ornamental garden method applied to buildings effectively uses resources efficiently. This study uses a descriptive qualitative method to describe alternative designs of space dividers and decorative designs with the concept of sustainable design.